Is mean platelet volume a predictive marker for sudden sensorineural hearing loss? - Emre Koçak, Hasan; Acıpayam, Harun; Keskin, Mehmet; Karaman Koç, Arzu; Pelin Yiğider, Ayşe; Tülin Kayhan, Fatma (ENT Updates, 2016)
Objective: There are many factors considered to be related with the etiology of sudden sensorineural hearing loss (SSNHL) such as viral infections, microvascular diseases and inflammation. Increased mean platelet volume (MPV) levels are assumed to represent more active enzymatic process and thrombotic predisposition. Our aim in this study is to show whether MPV could be a predictive value in SSNHL or not. Methods: The medical records of a total of 93 patients with SSNHL and 93 healthy controls were reviewed retrospectively in this study. Peripheral blood MPV values of both groups were compared statistically. Results: Mean platelet volume levels did not show a statistically significant difference between these groups. Conclusion: As a result of our study, we consider MPV is not a predictive parameter in idiopathic SSNHL.